2017
DOI: 10.4103/sjmms.sjmms_78_16
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of self-reported medical conditions among dental patients

Abstract: Background:In general, it is important to assess the medical history of patients before initiating any treatment. In particular, patients seeking dental treatment could possibly have significant medical conditions that may affect the diagnosis and/or alter the treatment provided. However, many dentists assume that their patients are systemically healthy, and thus they do not record the medical history of their patients.Aim and Objective:This study aimed to determine the prevalence of medical conditions in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
14
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 14 publications
6
14
2
Order By: Relevance
“… 25 Differences in environmental and genetic factors which affect disease epidemiology may be responsible for this variation. Unlike some scientific reports which showed hypertension and diabetes as the common medical conditions in dental patients, 20 26 the present study found peptic ulcer as the second most common medical conditions following hypertension. The association between poor oral hygiene and Helicobacter pylori as well as a greater prevalence of peptic ulceration has been reported in the literature.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“… 25 Differences in environmental and genetic factors which affect disease epidemiology may be responsible for this variation. Unlike some scientific reports which showed hypertension and diabetes as the common medical conditions in dental patients, 20 26 the present study found peptic ulcer as the second most common medical conditions following hypertension. The association between poor oral hygiene and Helicobacter pylori as well as a greater prevalence of peptic ulceration has been reported in the literature.…”
Section: Discussioncontrasting
confidence: 99%
“…Javali et al . 26 reported that 45% of medical problems in dental patients were found to be diabetic mellitus, while the gastrointestinal problem was only 5%, contrary to our finding. Immunosuppression and variation of these systemic conditions may be responsible for the differences.…”
Section: Discussioncontrasting
confidence: 99%
“…13,19,20,16 In this study, the highest age group was 17-35, and a large number of patients complained of diabetes and hypertension ( Table I). With regard to the participants who were aged 20-35 years and the high number of patients with diabetes and cardiovascular disease, similar result was obtained from a survey conducted by Javali et al in Abha region, 14 SA.…”
Section: Discussionsupporting
confidence: 79%
“…11 The risk for chronic form of periodontal disease increases with age, and the combined effect of age and oral hygiene standard explains more than 90% of the variation in periodontal disease. 12 Several local studies among different subpopulations in different areas of SA, namely, Abha, 13,14 Riyadh, 15,16 Jeddah, 17 Aljouf, 18 Al-Kharj, 19 Madinah, 20 and Jazan, 21,22 investigated the relationship of periodontal diseases with socio-economic, medical status of patients, awareness about periodontal diseases, and other local factors (smoking, shammah dipping, and khat chewing). Currently, no information is available regarding the pattern and distribution of periodontal disease among adult population in Jazan region, SA.…”
Section: Introductionmentioning
confidence: 99%
“…2 A consequential proportion of people with cardiovascular diseases are not identified when they visited dental clinic for treatment. 3 So, oral health care providers play a pivotal role in determining CVD in early stage.…”
mentioning
confidence: 99%